Phytochemical screening of mint leaves (Mentha sp.) as an innovation in biology learning - Anak Agung Istri Mas Padmiswari; Nadya Treesna Wulansari; Kadek Buja Harditya; Putu Indrayoni; Made Asmarani Dira (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
Phytochemistry-based practicums have the potential to strengthen students' cognitive understanding, psychomotor skills, and affective attitudes. This study examines the effectiveness of phytochemistry testing practicums using mint leaf (Mentha sp.) ethanol extract on the learning outcomes, psychomotor skills, and attitudes of biology students. The research subjects consisted of 30 second-year students selected using purposive sampling, as they had already completed the basic pharmaceutical biology course. A pre-experimental one-group pretest–posttest design was applied, with instruments including a learning outcome test, observation sheets, and a response questionnaire. The phytochemical screening results confirmed the presence of flavonoids, alkaloids, saponins, tannins, and terpenoids, which provided clear and easily observable visual indicators. Statistical analysis showed a significant increase in post-test scores compared to pre-test scores (p = 0.001). Observations revealed good performance in laboratory skills such as procedural accuracy, work safety, and teamwork, although color interpretation required further improvement. Questionnaire responses indicated that students perceived the practicum positively, particularly in terms of motivation, relevance to everyday life, and integration of theory with practice. These findings indicate that mint leaf-based phytochemistry practicums effectively support student learning, with an average score of 80.4 in the cognitive domain (Good–Very Good), 82 in the psychomotor domain (Good), and 85 in the affective domain (Very Good). The use of local plants as a practical medium also provides a contextual, low-cost, and innovative approach to biology education, with strategic potential to improve the quality of laboratory-based learning.Abstrak. Praktikum berbasis fitokimia berpotensi memperkuat pemahaman kognitif, keterampilan psikomotor, dan sikap afektif mahasiswa. Penelitian ini mengkaji efektivitas praktikum uji fitokimia menggunakan ekstrak etanol daun mint (Mentha sp.) terhadap hasil belajar, keterampilan psikomotor dan sikap mahasiswa biologi. Subjek penelitian terdiri dari 30 mahasiswa tahun kedua yang dipilih dengan teknik purposive sampling, karena telah menyelesaikan mata kuliah Biologi Farmasi Dasar. Desain penelitian yang digunakan adalah pra-eksperimental dengan rancangan one-group pretest–posttest, menggunakan instrumen berupa tes hasil belajar, lembar observasi, dan angket respon. Hasil skrining fitokimia mengonfirmasi adanya flavonoid, alkaloid, saponin, tanin, dan terpenoid yang memberikan indikator visual jelas dan dapat diamati dengan baik. Analisis statistik menunjukkan peningkatan signifikan pada nilai post-test dibandingkan pre-test (p = 0,001). Observasi menunjukkan keterampilan laboratorium mahasiswa berada pada kategori baik, khususnya dalam ketepatan prosedur, keselamatan kerja, dan kerja sama tim, meskipun interpretasi warna masih perlu ditingkatkan. Respon angket menunjukkan bahwa mahasiswa menilai praktikum ini secara positif, terutama dalam hal motivasi, relevansi dengan kehidupan sehari-hari, serta integrasi teori dengan praktik. Temuan ini menunjukkan bahwa praktikum fitokimia berbasis daun mint efektif mendukung pembelajaran mahasiswa dengan memperoleh rata-rata nilai 80,4 pada domain kognitif (Baik–Sangat Baik), 82 pada domain psikomotor (Baik), dan 85 pada domain afektif (Sangat Baik). Pemanfaatan tanaman lokal sebagai media praktikum juga menyediakan pendekatan kontekstual, berbiaya rendah, dan inovatif dalam pendidikan biologi, dengan potensi strategis untuk meningkatkan kualitas pembelajaran berbasis laboratorium.